Pengaruh Kemudahan dan Ketersediaan Fitur terhadap Penggunaan Mobile Banking - Johandri Iqbal; Heriyani Heriyani; Isroq Urrahmah (Global Financial Accounting Journal, 2021)
This study aims to analyze the effect of convenience and feature availability on the use of mobile banking at PT Bank Negara Indonesia (Persero) Tbk. This study uses a questionnaire as an instrument to take a sample of 100 respondents who are users of BNI Mobile Banking. The sampling method used is probability sampling. The analytical method used in this research is multiple linear regression analysis. The independent variables in this study, namely the convenience and availability of features, are able to explain the dependent variable, namely the use of mobile banking by 67%, the remaining 33% is determined or explained by other variables not included in this analysis or study. The results of this study indicate that the ease and availability of features have a significant effect on the use of mobile banking because it has a significance value <0.05 (0.001 for convenience and 0.001 for feature availability). And simultaneously the ease and availability of features have a significant effect on the use of mobile banking with a significance value of 0.000 <0.05.